Cooperation of rescue coordination centers in the event of an aircraft accident - Milić, Kristina (Crisis Management Days, 2025)
Introduction In the wake of an aircraft accident, the seamless coordination of rescue efforts among various entities is paramount to minimize loss of life and mitigate damages. The main point of this coordination is between in land rescue coordination centre and maritime rescue coordination centre, which plays critical roles in managing emergencies both on land and at sea. This paper delves deeper into the functions of these coordination centers and the collaboration required between them to ensure effective response and rescue operations. Rescue Coordination Centers in land (RCC), serve as coordination hub for managing emerency response activities following an aircraft accident. These center typically involve a multitude of stakeholders, including national, regional and local level authorities, emergency services, medical teams and aviation authorities. One of their primary functions is to facilitate emergency response coordination in the aircraft search and rescue operations, ensuring that various agencies work together seamlessly to address the search and rescue operation. Communication lies at the heart of land coordination center, acting as a vital conduit between different response teams and agencies involved in the rescue operation. With the established and maintained communication channels to enable the exchange of crucial information, coordinate efforts, and disseminate updates to all relevant parties involved in the rescue operation. Logistical support is another key responsibility of land coordination center. By overseeing the deployment of personnel, equipment, and resources to the accident site it is ensured that the necessary assistance reaches the affected area promptly and efficiently. This involves managing transportation logistics, coordinating with external organizations for additional support, and addressing any logistical challenges that may arise during the rescue operation. Information management is also a critical aspect of land coordination center function. Gathering, processing and disseminating accurate information about the accident to various stakeholders, including families of the victims, media outlets and relevant authorities are crucial elements. This ensures that everyone involved has access to timely and reliable information, helping to coordinate efforts effectively and manage crisis communication regarding the incident. Maritime Rescue Coordination Center (MRCC) is specifically tasked with managing maritime aspects of rescue operations, particularly in cases where the aircraft accident occurs over sea or in close proximity to coastlines. These center plays a crucial role in coordinating search and rescue efforts at sea, deploying vessels, aircraft and specialized teams to locate and assist survivors. Maritime Rescue Coordination Centre is the primary function of search and rescue operations in maritime environments, coordinating the deployment of resources and personnel to conduct search efforts efficiently and effectively. This may involve collaborating with other maritime agencies, such as coast guards and naval forces, to leverage their capabilities and assets for the rescue operation. They are also provide navigational support to vessels and aircraft involved in the rescue operation. This includes monitoring maritime traffic, providing guidance on safe navigation in the vicinity of the accident site and coordinating with relevant authorities to ensure the safety and security of rescue assets operting at sea. This paper will provide insight into collaboration between Rescue Coordination Center and Maritime Rescue Coordination Center which is essential for maximizing the effectiveness of search and rescue operations in aircraft accidents. This collaboration implies information sharing as the key aspect to ensure to both centers to have access to relevant and up - to - date information about the accident. This includes details such as the location of the accident, the number of survivors and any specific resource needs that may arise during the rescue operation. Joint planning and decision-making enable both centers to develop coordinated response strategies and make critical decisions regarding resource allocation, operational priorities and overall coordination of rescue efforts. This involves holding joint planning sessions, conducting regular briefings and maintaining open lines of communication between the two centers. Mobilization of the resources is facilitated through the jurisdiction of each coordination center. By pooling their resources and coordinating their efforts, they can ensure that the necessary personnel, equipment and assets are deployed to the accident site in a timely and efficient manner. Continuous communication is essential to maintain effective coordination between centers throughout the duration of the rescue operation. This involves establishing and maintaining communication channels that enable real-time updates, information sharing and coordination of efforts as well as with other relevant stakeholders involved in the rescue operation. In conclusion, effective collaboration between centers is essential for maximizing the chances of successful outcomes in aircraft search and rescue operations. By working together seamlessly and leveraging their respective expertise and resources, these centers ensure a swift, coordinated and effective response to emergency, ultimately saving lives and mitigating damages in the aftermath of an aircraft accident. Methodology For the purpose of this paper, methodology which will be use is literature review, data collection and data analysis in order to develop new operating procedure for mutual communiction between rescue coordination centers.